KETAHANAN PAPAN PARTIKEL TIGA LAPIS TERHADAP SERANGAN RAYAP TANAH - Janrahman Simarmata; Apri Heri Iswanto; Irawati Azhar (Peronema Forestry Science Journal, 2015)
The objective of this research was to evaluate the effect of wood species and adhesive type on durability three layers particleboard to subterranean termite attack. The research method using grave yard test on the field. Samples were oven dried before test, furthermore samples were burried for 3 month. After that, samples were washed, cleaned and oven dried.  Furthermore, the measuring of  weight sample to determine of weight loos parameter.The results showed that sengon and mahoni wood combination able to reduce of termite attack level compared with homogenous wood particleboard.  Sengon as surface layer and mahoni as core layer resulted the best durability of board.  The durability of UF adhesive for manufacturing particleboard better than combination UF and MF particleboard. Keywords:  Durability, Subterranean termite, particleboard, UF and MF